Comparison of Standard and Intensified Regimens for HIV-Negative Adults With Tuberculous Meningitis in West China: A Retrospective Observational Study - Abdulaziz, Ammar Taha Abdullah; Ren, Yi Meng; Li, Wei; Li, Jin Mei; Zhou, Dong (Frontiers in Neurology, 2019)
Background: Tuberculous meningitis (TBM) is an extremely devastating inflammation of the central nervous system; however, no available optimum treatment can effectively control the disease so far. Method: The medical records of TBM patients from May 2011 to August 2016 in West China hospital were retrospectively analyzed. Patients were divided into three groups based on their treatment regimens Group1: 4 standard therapy; Group2: 3 standard drugs + Levofloxacin; Group3: 4 standard therapy + Levofloxacin (G3a)/ Moxifloxacin (G3b). Using the intention-to-treat analysis, eventually, the treatments' efficacy and safety were compared among all groups. Results: Two hundred two patients with TBM were enrolled and followed up for at least 2 years. Among them, 99 patients were in G1; 18 in G2; and 85 in G3 (Moxifloxacin=39/ Levofloxacin=49). One hundred fifteen (56.9%) patients were males, and the median age was 42 years. At admission, 74 patients (36.6%) were in stage I, 102 (50.5%) in stage II and 26 (12.9%) in stage III. The most common symptoms were headache in 194 (96.0%) patients, fever in 162 (80.2%), vomiting in 120 (59.7%), neck stiffness in 104 (51.5%), and malaise in 96 (47.5%). The overall outcome at 1 year showed that 47 patients (47.5%) in G1, 10 patients (55.6%) in G2 and 48 patients (56.5%) in G3 had good outcome; however, there was no significant difference among all groups (P = 0.397); at 2 years there was also no difference among treatment groups (P = 0.295). However, in Group3b 22 patients (56.4%) at 1-year and 26 (66.7%) at 2-year follow up had a full recovery, which is significantly superior to other treatment groups, the P value at 1 and 2 years was 0.002 and 0.027, respectively. Conclusion: The overall outcome in patients with TBM at 1 and 2 years follow up did not show any statistically significant difference between the standard chemotherapy and other intensified regimens. Furthermore, Hydrocephalus (OR = 3.461, 95% CI: 1.349–8.882, P = 0.010) was the only independent risk factor for a poor outcome.